2018
DOI: 10.1002/adma.201706126
|View full text |Cite
|
Sign up to set email alerts
|

Stable and Efficient Organo‐Metal Halide Hybrid Perovskite Solar Cells via π‐Conjugated Lewis Base Polymer Induced Trap Passivation and Charge Extraction

Abstract: High-quality pinhole-free perovskite film with optimal crystalline morphology is critical for achieving high-efficiency and high-stability perovskite solar cells (PSCs). In this study, a p-type π-conjugated polymer poly[(2,6-(4,8-bis(5-(2-ethylhexyl) thiophen-2-yl)-benzo[1,2-b:4,5-b'] dithiophene))-alt-(5,5-(1',3'-di-2-thienyl-5',7'-bis(2-ethylhexyl) benzo[1',2'-c:4',5'-c'] dithiophene-4,8-dione))] (PBDB-T) is introduced into chlorobenzene to form a facile and effective template-agent during the anti-solvent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
153
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(160 citation statements)
references
References 77 publications
5
153
0
Order By: Relevance
“…[18] Meanwhile, these trap states create conditions for the infiltration of moisture and oxygen into perovskite layer and subsequently seriously decrease the device stability. Additive engineering [26][27][28][29][30][31][32][33][34] and interface engineering [35][36][37][38][39][40][41] have been regarded as effective strategies to reduce the defect density in PSCs, such as incorporating Phenyl-C61-butyric acid methyl ester (PCBM) [29] into perovskite layer to effectively passivate the defects and minimize the photocurrent hysteresis, inserting self-assembled monolayer of organic molecules with functional groups [36,37] into perovskite/ETL interface to suppress defects Defects, inevitably produced within bulk and at perovskite-transport layer interfaces (PTLIs), are detrimental to power conversion efficiency (PCE) and stability of perovskite solar cells (PSCs). [23][24][25] Therefore, it is imperative to seek an effective way to reduce the defects, especially at the PTLIs, for achieving the high-performance PSCs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[18] Meanwhile, these trap states create conditions for the infiltration of moisture and oxygen into perovskite layer and subsequently seriously decrease the device stability. Additive engineering [26][27][28][29][30][31][32][33][34] and interface engineering [35][36][37][38][39][40][41] have been regarded as effective strategies to reduce the defect density in PSCs, such as incorporating Phenyl-C61-butyric acid methyl ester (PCBM) [29] into perovskite layer to effectively passivate the defects and minimize the photocurrent hysteresis, inserting self-assembled monolayer of organic molecules with functional groups [36,37] into perovskite/ETL interface to suppress defects Defects, inevitably produced within bulk and at perovskite-transport layer interfaces (PTLIs), are detrimental to power conversion efficiency (PCE) and stability of perovskite solar cells (PSCs). [23][24][25] Therefore, it is imperative to seek an effective way to reduce the defects, especially at the PTLIs, for achieving the high-performance PSCs.…”
mentioning
confidence: 99%
“…www.advmat.de www.advancedsciencenews.com and optimize energy alignment, as well as introducing organic polymer with hydrophobic groups [38,40] into perovskite/HTL interface to passivate the defects on the surface of perovskite layer. Although there are many passivation materials currently to reduce the defect density, it has not been reported that the defects in the perovskite bulk, as well as at PTLIs can be simultaneously passivated via only one material.…”
mentioning
confidence: 99%
“…Trioctylphosphine oxide (TOPO) and triphenylphosphine oxide (TPPO) were also reported as O‐donor Lewis bases to passivate MHP films effectively, resulting in an extended carrier lifetime of 8 µs and improved PCE (Figure c) . Other Lewis bases such as fullerene, π‐conjugated IDIC and PBDB‐T, non‐fullerene acceptor IT‐M, 2,6‐dimethoxypyridine, caprolactam, thiourea, and fluorine‐containing hydrophobic Lewis acid have also demonstrated success. Recently, Gao et al reported an unencapsulated devices with an active area of 1.0 cm 2 retaining 93% of the original PCE of 17.67% after 2 months under air conditions.…”
Section: Interfacial Modification Layersmentioning
confidence: 99%
“…[7] Also, ion migration and accumulation at the external interface is thought to be responsible for the observed hysteresis behaviors. [14] Non-negligible loss of halide ions or undercoordinated Pb 2 + in MAPbI 3 films near the interface with the ETL contributes to more traps duringp erovskite annealing and crystallization, which reduces the carrierc ollection. [9][10][11] These approaches improvet he perovskite film quality,r educe the hysteresis behavior,a nd enhancet he overall efficiency through facilitating carrier transport at the electron transport layer (ETL)/perovskite interface and passivating the perovskite layer.O ne of the main challenges for scaled-up productiono fp erovskite solar cells is the device stability:t his issue can be addressed by interfacial engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Although complicated organic molecules [10,15] were employed to realize rapid charget ransfer at the interface and suppress hysteresis, potentiald efects in the interconnections among organicm olecules limit the effectiveness of the interfacial trap passivation, [14] which is unfavorable for photovoltaic device performance or stabilityi na mbient environment. Inorganic sulfur functionalization on the SnO 2 ETL was introduced through xanthate decomposition at low temperature to modify the SnO 2 /perovskite interface to anchor Pb 2 + in perovskite and SnO 2 simultaneously, leading to improved charge transport as ar esult of chemical interactions at the SnO 2 /perovskite junction.…”
Section: Introductionmentioning
confidence: 99%